Effect of Assessment Practices on Teaching Contents at Secondary Level (Journal of Social Sciences Review, 2023)
Assessment practices play a dynamic role in the educational development through teaching contents. These contents affects the academic performance of students. That is why external examinations are conducted at secondary level to assess the students’ academic achievements in Pakistan. These external examinations in Pakistan have always been criticized due to pedagogical practices. These pedagogical practices affected by assessment practices. Hence, this research study was proposed to find the effects of assessment practices on teaching contents. Question papers at secondary level are major tools of assessment. This research finds that existing assessment practices encourages remembering and cramming. Text books are commonly focused by teachers for teaching purposes. Selective contents are encouraged and speaking skills are discouraged for preparation of examinations. This research study concluded that assessment practices at secondary level effects teaching contents.
Keywords: Assessment; Question Papers; Oral Communications; Text Book Contents; Teaching Contents, Cramming